(untitled) (Delta Medical College Journal, 2020)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal (subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Pharmacologically induced tranquility improves acceptance of regional technique. Objective: This study compares Fentanyl and Ketofol (Ketamine+Propofol) in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal anaesthesia. Materials and method: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I patients between age 20-40 years undergoing elective Caesarean sections under subarachnoid anaesthesia during the period January 2022 to June 2022. Patients were randomly allocated to one of two groups: Fentanyl group (Group F, n=30), who received Fentanyl in a single dose of 0.5mcg/kg and Ketofol group (Group KP, n=30), who received Ketofol in a single dose of 0.5mg/kg (Ketamine-0.5mg/kg+ Propofol-0.5mg/kg). Spinal anaesthesia was conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset of sedation i.e. time from iv (intravenous) injection of Fentanyl or Ketofol to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 ( patient is awake clinically) were noted. Any complication during operation was documented. The patient’s satisfaction with the sedation was assessed by the 5 point ‘Likert verbal rating scale. Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (p>0.05). Time of onset of sedation was significantly less with Ketofol than Fentanyl (p<0.05). The arousal time i.e. duration of sedation was significantly longer with Ketofol than Fentanyl (p<0.05). Fentanyl was associated with high incidence of some adverse effects like nausea, vomiting than Ketofol (46.66% vs 16.70%, p<0.05). Pain in arm during drug administration was significantly more with Ketofol (33.33% vs 6.66%, p<0.05). Significant percentage of patients was satisfied with Ketofol than Fentanyl (66.66% vs 20%, p<0.001). Conclusion: The study showed that the time to reach effective sedation was less with Ketofol than Fentanyl and the arousal time i.e. duration of sedation was significantly longer with Ketofol which is beneficial for the patient in single dose technique for sedation. Although incidence of pain in arm was more with Ketofol, Fentanyl was associated with high incidence of some adverse effects like nausea and vomiting. Thus it is recommended that Ketofol is a better choice than Fentanyl for sedation in single dose technique during subarachnoid block for Caesarean section. Delta Med Col J. Jul 2020;8(2): 67-74